Error Analysis of Students in Chinese Language Education Program in Writing Hànzì Characters - Marsuki, Ria Riski; Fatmawati, Fatmawati (Universitas Negeri Semarang, 2024)
One of the essential skills that students in the Chinese Language Education program need to master is the ability to write hànzì characters, as Mandarin writing has unique characteristics different from the Indonesian language. This poses the greatest challenge in writing and presents a distinct challenge for the future development of Chinese. The aim of this research is to identify the types of errors in writing hànzì strokes and the factors influencing these errors. The method used is descriptive qualitative. The data consists of 16 student writings collected through observation, documentation, and interviews. This research categorizes students' writing errors into four groups and identifies internal and external factors influencing these errors.